KELANGSUNGAN HIDUP, PERTUMBUHAN DAN EFISIENSI PAKAN IKAN GABUS (Channa striata) YANG DIBERI PAKAN BERBAHAN BAKU TEPUNG KEONG MAS (Pomacea sp) - Deny Hidayat; Ade Dwi Sasanti; Yulisman . (Jurnal Akuakultur Rawa Indonesia, 2013)
The purpose to know influence feed from golden apple snail flour for survival, growth, and feed efficiency of snake head (C. striata). There search used completely randomized design with five treatments and three replications. The treatments were AR 1 (0 % golden apple snail flour : 50 % fish flour), AR 2 (12.5 % golden apple snail flour : 37.5 % fish flour), AR 3 (25 % golden apple snail flour : 25% fish flour), AR 4 (37.5 % golden apple snail flour : 12.5% fish flour) and AR 5 (50% golden apple snail flour : 0 % fish flour). The parameters observed were survival rate, absolute weight growth, absolute length growth and feed efficiency.The results of this research showed that the highest survival ratewas 86.67 % (AR 4). The highest bsolute weight and length growth was 4.96 g and 0.9 cm (AR 5). Whereas, the highest feed eficiency was 29.45 % (AR 1). In observation histology of snake head found hemoragi and nekrosit hepatosit in all treatment, before treatment and AR 1, AR 2, AR 4 dan AR 5 found congesti at snake head, whereas fat degeneration at snake head before treatment. Â  Key words : Snake head, golden apple snail flour